Plasma trace elements, vitamin B12, folate, and homocysteine levels in cirrhotic patients compared to healthy controls - Halifeoglu, I; Gur, B; Aydin, S; Ozturk, A (Pleiades Publishing Ltd, 2004)
Increased serum homocysteine (Hcy) can induce liver diseases and can play a remarkable role in hepatic disorders. The purpose of the present study therefore was to investigate the relationship between serum vitamin B-12, folate, zinc and copper, cysteine, and Hcy level differences between cirrhotic patients and healthy subjects. We studied 32 cirrhotic patients (12 females and 20 males) aged 45 +/- 11 years and 32 control subjects (12 females and 20 males) aged 39 +/- 9 years. There was an inverse correlation between Hcy and vitamin B-12 in controls (r = -0.442, p < 0.011) but not in cirrhotic patients (r = -0.147, not significant). Also, mean plasma folate was decreased in cirrhotic patients compared to controls (p < 0.001). Copper increased whereas zinc decreased significantly in cirrhotic patients. A positive correlation was seen between the Cu/Zn ratio and Cu in controls (r = 0.690, p < 0.01), but the correlation between the Cu/Zn ratio and Cu was not significant in the cirrhotic group. Negative correlations were seen between plasma concentration of zinc and the Cu/Zn ratio in controls and cirrhotic patients (r = -0.618, p < 0.01 and r = -0.670, p < 0.01, respectively). Cirrhotic patients displayed multiple abnormalities, including changes in cysteine metabolism and in zinc and copper levels. Although hyperhomocysteinemia is known as an atherogenic and thrombogenic risk factor for cardiovascular disease, it might also be a risk factor for cirrhotic patients. Plasma Hcy, vitamin B-12, and folic acid measurement may be useful in the evaluation of cirrhotic patients.
Keywords: cirrhosis; homocysteine; folate; vitamin B-12